Niacin esters of chalcones with tumor-selective properties. (1st November 2016) - Panda, Atulya K.; Das, Umashankar; Roayapalley, Praveen K.; Sakagami, Hiroshi; Kawase, Masami; Balzarini, Jan; De Clercq, Erik; Dimmock, Jonathan R.
Abstract: Novel series of niacin esters of chalcones2, 4 and6 were designed as antineoplastic agents that have the potential to release the chemoprotectant niacin. These enones are cytotoxic to human CD4 +  T-lymphocyte Molt 4/C8 and CEM and murine leukemia L1210 cells. Quantitative structure–activity relationship (QSAR) studies of the biodata in series4 revealed that cytotoxic potency was enhanced by placing electron-repelling groups in one of the aryl rings. The compounds are lethal to HL-60, HSC-2, HSC-3 and HSC-4 neoplasms but less toxic to nonmalignant hepatocyte growth factor, hematopoietic progenitor cell and human periodontal ligament fibroblast cells. Hence, the compounds display tumor-selective toxicity. These chalcones are well tolerated in mice and no overt toxicity was noted. The results establish that in general the compounds in series2, 4 and6 have positive characteristics which warrant further studies.